(untitled) (Medical Forum Monthly, 2024)
ABSTRACT Objective: To study the prevalence of G6PD deficiency and coombs test positivity in newborn presenting with hyperbilirubinema. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at the Paediatric Department of Bacha Khan Medical College & Mardan Medical Complex Teaching Hospital Mardan from January 2017 to July 2018. Materials and Methods: A total of hundred newborn with hyperbilirubinama and fifty healthy newborns as a control group were included in the study. All the newborns were subjected to G6PD test, coombs test, Retic count, full blood count, blood groups and total, direct, indirect bilirubin level. Results: A total of 9% Newborn with hyperbilirubinema showed G6PD Deficiency. Mean bilirubin level was 25±2.562 mg/dl, significantly elevated as compared to control group. P<0.00236. Similarly 10% newborn showed coombs test positive and these were Rh incompatible. Mean bilirubin level was 26±2.156 mg/dl, significantly higher as compared to control group. P<0.000326. 80% Newborn had physiological jaundice. Mean bilirubin level were 13±2.562 mg/dl, significantly higher than control group.P< 0.00422. Conclusion: The study concluded that Newborn presenting with hyperbilirubinamais significantly associated with high prevalence of G6PD deficiency and positive coombs test which indicates Rh-incompatibility. Therefore all the Pediatrician should have priority to screen all newborn presenting with hyperbilirubinamafor G6PD deficiency and coombs test. As these two conditions are very common in Pakistan this will early identify newborn with hyperbilirubinemia leading to serious complication like kernicterus.